The Relationship Between Stock Returns and Rates of Inflation in Czech Republic - Nardelli, Alexander (2024)
This research investigates the relationship between inflation and stock returns in the Czech Republic, focusing on the Fisher Hypothesis. Utilizing PX Index from Prague Stock Exchange and CPI for the period of 2001 - 2003 and employing empiric methods such as Johansen cointegration tests, Vector Error Correction model and Autoregressive Distributed Lag model, the study finds that nominal PX returns exhibit a significant negative relationship with inflation rates, contrary to the traditional view of stocks as inflation hedges. Real PX returns show weak and statistically insignificant responses to inflation, underscoring the complexities of the the Fisher Puzzle. These findings contribute to the broader discourse on, offering region-specific insights for investors and policymakers.